Factors influencing clinical decision making used by mental health nurses to provide provisional diagnosis: A scoping review. (4th November 2018) - Campbell, Katrina; Massey, Deb; Broadbent, Marc; Clarke, Karen‐Ann
Abstract: Medical diagnosis has traditionally been the role of medical officers. However, mental health nurses working in crisis/emergency settings within Australia are expected to provide a provisional diagnosis postassessment of a consumer. There is limited literature and understanding how mental health nurses develop a provisional diagnosis. In this scoping review, we aimed to first identify and describe the clinical decision‐making processes used by mental health nurses across a variety of clinical settings. Second, we sought to explore the factors influencing mental health nurse's diagnostic practice in a variety of settings. Literature was searched using CINAHL (EBSCOhost), PubMed, and ProQuest. Peer‐reviewed literature published between 2007 and 2017 was used for this scoping review. Two major themes were identified: clinical decision making (CDM) in mental health nursing and diagnostic practice in nursing. A combination of clinician, environmental, and patient factors were found to have influenced CDM. Furthermore, mental health nurses rely heavily on tacit knowledge when making clinical decisions. Little is known about the use of diagnostic practice in mental health nursing in Australia; however, the limited literature revealed an overlap between the factors which influence CDM and diagnostic practice, respectively. Further research is needed into the use of diagnostic practice in mental health nursing to develop frameworks to assist with CDM pertaining to application of provisional diagnosis by mental health nurses working in assessment environments.